Hypofractionated Irradiation Suppressed the Off-Target Mouse Hepatocarcinoma Growth by Inhibiting Myeloid-Derived Suppressor Cell-Mediated Immune Suppression - Chen, Junying; Wang, Zeng; Ding, Yuxiong; Huang, Fei; Huang, Weikang; Lan, Ruilong; Chen, Ruiqing; Wu, Bing; Fu, Lengxi; Yang, Yunhua; Liu, Jun; Hong, Jinsheng; et al. (Frontiers in Oncology, 2020)
Background: Stereotactic radiotherapy treats hepatocellular carcinoma (HCC) at different stages effectively and safely. Besides its direct killing of cancer cells, radiotherapy stimulates host immunity against hepatoma. However, the role of myeloid-derived suppressor cells (MDSCs) in on-target and off-target anti-HCC effects induced by hypofractionated irradiation (IR) is unclear. Methods and Materials: Hepa1-6 and H22 allogeneic transplanted tumors on hind limbs of C57BL/6 and Institute of Cancer Research (ICR) mice, respectively, were irradiated with 0, 2.5, 4, 6, or 8 Gy/fraction until the total dose reached 40 Gy. The off-target effect induced by the IR was investigated by subsequently inoculating the same HCC cells subcutaneously on the abdomen. MDSCs in peripheral blood and tumor tissues were measured by flow cytometry or immunofluorescence microscopy analysis. IL-6, regulated on activation normal T cell expressed and secreted (RANTES), and granulocyte colony-stimulating factor (G-CSF) in irradiated mouse plasma and hepatoma cell cultures were measured with ELISA kits. Conditioned media (CM) from irradiated HCC cell cultures on bone marrow cell differentiation and MDSC proliferation were examined by co-culture and flow cytometry. Results: Our study showed that the IR of primarily inoculated HCC on hind limbs created an “in situ tumor vaccine” and triggered the antitumor immunity. The immunity was capable of suppressing the growth of the same type of HCC subcutaneously implanted on the abdomen, accompanied with reduced MDSCs in both blood and tumors. The decreased MDSCs were associated with low plasma levels of IL-6, RANTES, and G-CSF. The cytokines IL-6 and RANTES in the CM were lower in the high single IR dose group than in the control groups, but G-CSF was higher. The CM from high single-dose IR-Hepa1-6 cell culture reduced the differentiation of C57BL/6 mouse bone marrow cells into MDSCs, whereas CM from high single-dose IR-H22 cells reduced the proliferation of MDSCs, which might be due to the decreased p-STAT3 in bone marrow cells. Conclusions: The hypofractionated IR on transplanted tumors at the primary location exerted a strong antitumor effect on the same tumor at a different location (off target). This abscopal effect is most likely through the reduction of MDSCs and decrease of IL-6, RANTES, and G-CSF.